BRUXA ONILDA E A MACACA - LARREULA I VIDAL, ENRIC; CAPDEVILA, R. (SAO PAULO SCIPIONE, 1991)
Bruxa Onilda arruma uma aprendiz tão atrapalhada quanto ela.
PORTUGUES
Keywords: LITERATURA INFANTOJUVENIL; LIVRO